FLUID REPLACEMENT IN TEENS ATHLETE SWIMMING IGUAÇU FOZ CITY (Fiep Bulletin - online, 2017)
Introduction: Adequate hydration during physical activity can ensure expected performance and prevent healthproblems. This study aims to check hydration in swimming athletes during training. Methods: Seventeen swimmers aged betweenten and sixteen. The hydration state was determined by the urinary staining, the percentage loss of body weight, clinical evaluationof signs and symptoms. Results: Based on body weight and symptoms and signs 58.82% (n = 10) sample showed weight loss of 1%to 2% and 42.17% (n = 7) showed a weight loss lower than 1 0%. The result of staining urinary not coincided with the previous results.The average sweat rate of 4.9 (ml / min). The fluid intake was on average 624 ml / min, and the temperature of the liquid variedbetween 3 ° C to 23 ° C. 41.1% (n = 7) of the sample held water intake, 35.2% (n = 6) maltodextrin, 11.7% (n = 2) and Gatorade 11.7%(n = 2) without beverage. Conclusion: According to the percentage of the results the majority of the study sample showeddehydration in relation to body mass, signs and symptoms. Moreover, the results indicate that the consumption of drink withtemperature, type and quantity was inadequate. It was found that the assessment of urine color does not seem to be a reliablemethod can be changed to other factors. Regarding the sweating rate, the results were consistent with other studies, and this is notprimarily responsible for heat loss.